Fractography and Failure Analysis - González-Velázquez, Jorge Luis (Structural Integrity,, 2018)
This book presents fractography and failure analysis at a level that is accessible for non-expert readers, without losing scientific rigor. It offers a comprehensive description of fracture surfaces in engineering materials, with an emphasis on metals, and of the methodology for the observation of fracture surfaces. It also discusses in detail the main fracture mechanisms and their corresponding fracture surfaces, including brittle, ductile, fatigue, and environmental fractures. The last chapter is dedicated to the use of fractography in determining of the causes component failure. In modern engineering, the analysis of fractured components is a common practice in many fields, such as integrity management systems, materials science research, and failure investigations. As such this book is useful for engineers, scientists, engineering students, loss adjuster surveyors and any professional dealing with fractured components.